2014
DOI: 10.1158/1055-9965.epi-13-1251
|View full text |Cite
|
Sign up to set email alerts
|

Associations between 25 Lung Cancer Risk–Related SNPs and Polycyclic Aromatic Hydrocarbon–Induced Genetic Damage in Coke Oven Workers

Abstract: Background: Genome-wide association studies (GWAS) have identified multiple single-nucleotide polymorphisms (SNP) associated with lung cancer. However, whether these SNPs are associated with genetic damage, a crucial event in cancer initiation and evolution, is still unknown. We aimed to establish associations between these SNPs and genetic damage caused by the ubiquitous carcinogens, polycyclic aromatic hydrocarbons (PAH).Methods: We cross-sectionally investigated the associations between SNPs from published … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…We did not find any significant differences in levels of plasma BPDE‐Alb adducts and lymphocytic MN frequencies between smokers and non‐smokers in this occupational cohort. A possible reason was that when comparing with cigarette smoking, coke oven emissions contain much higher concentrations of PAHs, which may cover the role of smoking in generating BPDE‐Alb; moreover, the genetic damage of coke oven workers in the current study might be determined by high‐occupational exposure to PAHs rather than tobacco smoke, which was also consistent with results of our recent studies .…”
Section: Discussionsupporting
confidence: 90%
“…We did not find any significant differences in levels of plasma BPDE‐Alb adducts and lymphocytic MN frequencies between smokers and non‐smokers in this occupational cohort. A possible reason was that when comparing with cigarette smoking, coke oven emissions contain much higher concentrations of PAHs, which may cover the role of smoking in generating BPDE‐Alb; moreover, the genetic damage of coke oven workers in the current study might be determined by high‐occupational exposure to PAHs rather than tobacco smoke, which was also consistent with results of our recent studies .…”
Section: Discussionsupporting
confidence: 90%
“…In a study from China [34], coke oven workers were found to have 25 lung cancer risk related SNPs which correlated with polycyclic hydrocarbon induced genetic damage. In a study of variants of the nicotinic receptor genes and the association with both smoking dependence and adenocarcinoma of the lung, two CHRNA3 SNPs were most associated with nicotine dependence and adenocarcinoma of the lung [35].…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified multiple single-nucleotide polymorphisms (SNPs) associated with lung cancer. Lung cancer risk-associated SNPs and their correlations with PAH exposure were associated with 8-OHdG levels and Micronuclei (MN) frequency [38]. PAHs are established lung carcinogens and may cause mitochondrial toxicity.…”
Section: Biomarkers and Coke Oven Workersmentioning
confidence: 99%
“…These researchers established associations between SNPs and genetic damage caused by polycyclic aromatic hydrocarbons (PAHs). Lung cancer risk-associated SNPs and their correlations with PAH exposure were associated with urinary 8-hydroxydeoxyguanosine (8-OHdG) levels and micronucleus (MN) frequency [38].…”
Section: Relationship Between Different Biomarkers and Vital Statusmentioning
confidence: 99%